Acupuncture therapies for post-stroke depression: the evidence mapping of clinical studies - Zhou, Zhuo; Ke, Chao; Shi, Wenying; Cao, Yang; Xie, Zhengrong; Zhao, Xi; Hu, Zeli; Zhou, Yilin; Zhang, Wei (Frontiers in Psychiatry, 2025)
BackgroundAcupuncture-related therapies have been widely used in previous studies, of which the ones for post-stroke depression (PSD) is on the rise. This study aims to map the current clinical research landscape and identifies gaps to provide direction and information for future research.MethodsEight databases were searched on acupuncture-related therapies for PSD from inception until April 2024. The publication profile, study objects, intervention categories, outcome indexes were graphically displayed. The Cochrane Collaboration’s bias risk assessment tool was used to independently assess randomized controlled trials (RCTs) quality, and the methodological quality of the systematic reviews were assessed using the AMSTAR 2 checklist.ResultsA total of 666 clinical studies and 34 systematic reviews/Meta-analyses (SRs/MAs) were included in the evidence map, and the earliest report was found in 1996. The studies were mostly from China, and 89% of the evidence of the studies were of the RCTs. Body acupuncture and electroacupuncture were the most commonly used interventions. Most of the intervention durations were 2-4 weeks, and few patients were followed up. The main outcome was measured by effective rate and the Hamilton Rating Scale for Depression (HAMD). Evidences from clinical studies and SRs/MAs suggest that acupuncture has significant advantages in improving PSD, but the overall quality of studies could be improved.ConclusionsAcupuncture-related therapies have great prospect in relieving the clinical symptoms of PSD, although there are some design and methodological defects in the current studies. In the future, the quality of research needs to be improved for the robustness of clinical evidence.